The Effect of a Deep Learning Instructional Approach Supported by Animated PowerPoint Media on Junior High School Students' Numeracy Literacy Skills - Yasri, Bayhaqi; Siregar, Tanti Jumaisyaroh (Desimal: Jurnal Matematika, 2026)
Numeracy literacy has become a fundamental competency for enabling students to interpret quantitative information, construct mathematical representations, and make informed decisions in authentic contexts. Despite its importance, many junior high school students continue to experience difficulty applying mathematical concepts beyond routine procedural tasks, indicating the need for instructional approaches that promote deeper conceptual understanding. This study investigated the effect of a Deep Learning instructional approach supported by animated PowerPoint media on students’ numeracy literacy skills while examining how progressive visual scaffolding enhances meaningful mathematical learning. A quantitative quasi-experimental study employing a pretest–posttest control group design was conducted with 61 eighth-grade students at SMP Negeri 2 Namorambe, Indonesia, selected through cluster random sampling and assigned to an experimental group (n = 32) and a control group (n = 29). Data were collected using a validated essay-based numeracy literacy test and analyzed through descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, an independent-samples t-test, and Cohen’s d. Students receiving the Deep Learning instructional approach significantly outperformed those receiving conventional instruction, achieving a posttest mean of 74.09 compared with 51.07 in the control group, t(59) = 5.514, p < .001, with a large effect size (d = 1.414). The findings contribute empirical evidence that pedagogical integration, rather than technological sophistication alone, is the principal mechanism through which technology enhances numeracy-oriented mathematics learning in lower-secondary education.